Research on the improved algorithm for image quantum encryption in multimedia networks. (August 2017) - Wang, Bo; Xu, Jing; Song, Houbing
Highlights: This paper presents an improved algorithm for image quantum encryption and analyzed the classic imageencryption method. Considering the disadvantages of the classical encryption method, we improve it by the quantum encryption method. Introduced the physical basis of key generation and distribution in image quantum encryption, analyzed the single particlekey distribution algorithm and the two particle entangled state key distribution algorithm. Judged whether there is an effective way of intercepting by using two key distribution algorithms, which could make the communicating parties complete key negotiation by using the unreliable channels, make sure that the key is absolutely safe, ensure the security of the image. The experimental results show that the proposed method has high encryption performance, and the security and the ability to resist differential attacks are also very high. Abstract: The current image encryption methods do not take into account the characteristics of images, and these algorithms require higher hardware resources. Therefore, this paper presents an improved algorithm for image quantum encryption. Based on the analysis of the classic image encryption method, the physical basis of key generation and distribution of image quantum encryption are introduced, and the single particle key distribution algorithm and the two particles entangled state key distribution algorithm are analyzed. To Judge whether there is an effective way by using two key distribution algorithms, so that it can make the both communicating sides (Alice and Bob) to complete key negotiation and generation by using the unreliable channels, making sure that the absolutely safe of key, and ensuring the security of the image. The experimental results show that the proposed method has high encryption performance, and the security and the ability to resist differential attacks are also very high. Graphical abstract: